2004
DOI: 10.1111/j.1365-2958.2004.04178.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Stagonospora nodorum requires malate synthase

Abstract: SummaryA gene encoding malate synthase, a key enzyme of the glyoxylate cycle, has been cloned and characterized in the necrotrophic wheat pathogen Stagonospora nodorum . Expression studies of Mls1 showed high levels of transcript in ungerminated spores whereas malate synthase enzyme activities were low. Expression studies in planta found that Mls1 transcript levels decreased ª ª ª ª 10-fold upon germination before slowly increasing throughout the remainder of the infection. To characterize Mls1 further, the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
90
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 22 publications
3
90
0
Order By: Relevance
“…nodorum is an experimentally tractable organism, which is easily handled in defined media, was one of the first fungal pathogens to be genetically manipulated (Cooley et al, 1988), and has been a model for fungicide development (Dancer et al, 1999). Molecular analysis of pathogenicity determinants is aided by facile tools for gene ablation and rapid in vitro phenotypic screens, and thus far, a small number of genes required for pathogenicity have been identified (Cooley et al, 1988;Bailey et al, 1996;Bindschedler et al, 2003;Solomon et al, 2003bSolomon et al, , 2004aSolomon et al, , 2004bSolomon et al, , 2005Solomon et al, , 2006a. It has thus emerged as a model for dothideomycete pathology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…nodorum is an experimentally tractable organism, which is easily handled in defined media, was one of the first fungal pathogens to be genetically manipulated (Cooley et al, 1988), and has been a model for fungicide development (Dancer et al, 1999). Molecular analysis of pathogenicity determinants is aided by facile tools for gene ablation and rapid in vitro phenotypic screens, and thus far, a small number of genes required for pathogenicity have been identified (Cooley et al, 1988;Bailey et al, 1996;Bindschedler et al, 2003;Solomon et al, 2003bSolomon et al, , 2004aSolomon et al, , 2004bSolomon et al, , 2005Solomon et al, , 2006a. It has thus emerged as a model for dothideomycete pathology.…”
Section: Introductionmentioning
confidence: 99%
“…The hyphae rapidly colonize the leaves and begin to produce pycnidia in 7 to 10 d. The infection has been divided into three metabolic phases (Solomon et al, 2003a). The first phase is penetration of the host epidermis and is fuelled predominantly by lipid stores in the spores (Solomon et al, 2004a); the second is proliferation throughout the interior of the leaf, involves toxin release , and uses hostderived simple carbohydrate sources (Solomon et al, 2004a); the final phase produces the new spores, but so far the metabolic requirements for pycnidiation are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The glyoxylate cycle plays an important role in the nutrition of both plant-and animal-pathogenic fungi. These include plant pathogens Magnaporthe grisea (88), Leptosphaeria maculans (42), and Stagonospora nodorum (76) and animal pathogens such as C. albicans (51) and Aspergillus fumigatus (27). Fungal mutants with mutations in the glyoxylate cycle enzymes isocitrate lyase or malate synthase have low levels of germination and are not infectious.…”
Section: Developmental Regulation Of Pathogenesismentioning
confidence: 99%
“…is a major pathogen of wheat and other cereals (Solomon et al, 2006d) causing stagonospora nodorum blotch (previously septoria nodorum blotch and glume blotch). Previous studies focused on understanding the disease have demonstrated critical roles for host-specific toxins and various primary metabolic pathways for effective fungal pathogenicity (Solomon et al, 2004a;Solomon et al, 2005a;Solomon et al, 2006a;Solomon et al, 2006e).…”
Section: Introductionmentioning
confidence: 99%